Towards direct metal laser fabrication of Cu-based shape memory alloys. Issue 2 (20th March 2017) - Reyes Donoso, Gonzalo; Walczak, Magdalena; Ramos Moore, Esteban; Ramos-Grez, Jorge Andres
Abstract : Purpose: The purpose of this paper is to explore the possibility of producing Cu-based shape memory alloys (SMA) by means of direct metal laser fabrication (DMLF). Design/methodology/approach: The fabrication approach consists of the combination of laser melting of a metallic powder with heating treatment in a controlled inert atmosphere. Three prospective Cu-Al-Ni alloy compositions were tested, and the effects of laser power, as well as laser exposure time, were verified. Findings: All the processed materials were found to attain microstructures and phase change transformation temperatures typical of this type of SMA. Practical implications: Further development of this technique will allow for fabrication of large elements with considerable shape memory effect, which are currently not viable due to high cost of nitinol. Originality/value: This work showed a proof of concept toward the development of DMLF-based additive manufacturing of near net shape components of Cu-based SMAs from elemental powders.